Look-alike and sound-alike medicines: let us all be aware - Dixit, Sanjaya Mani (Journal of Kathmandu Medical College, 2014)
Background: ALMEX and ALMOX; ASOM and AZOM; TRIAD, TRIAD P and TRIAD PF; folic acid and folinic acid; Vincristine and Vinblastine. Such look-alike and sound-alike medicines because of the similarity in their names create confusion while dispensing and administration/consumption of medicine. This may eventually cause varied degree of harm to the patient resulting from inadvertent consumption of an unintended drug. Objective: This study was conducted to analyze and list out common confusing drug pairs in the Nepalese market aiming to increase awareness of such drug pairs among health care professionals. Methods: Department of Drug Administration list of registered drugs, Nepal Drug Review, Monthly Index of Medical Specialties and findings from drug survey in the market were used as sources of the drugs analyzed in this study. Error prone medication pairs that cause confusion while prescribing, dispensing and administration/consumption were sorted out manually. Results: Such drug-pairs were regrouped into different categories in a manner that they depict the clinical significance of the type of error. Also real life experiences of medication errors and near misses due to error prone drug pairs were collected from the doctors and the dispensers. Conclusion: Several brand names are nearly identical; look alike sound alike drug pairs pose as an imminent danger to medical practice. This problem can only be minimized by increasing awareness of the presence of such confusing drug pairs among the healthcare professionals and increasing the feeling of shared responsibility by all the core members of the health care team. DOI: http://dx.doi.org/10.3126/jkmc.v2i2.10630 Journal of Kathmandu Medical College, Vol. 2, No. 2, Issue 4, Apr.-Jun., 2013, page: 75-83